Floristic mosaics of the threatened Brazilian campo rupestre - Caminha-Paiva, Dario; Gomes, Vanessa M.; Cunha-Blum, Jessica; Alves, Michel J. P.; Rosa, Dian C. P.; Santiago, Júlio C.; Negreiros, Daniel; Fernandes, G. Wilson (Nature Conservation Research: Заповедная наука, 2022)
The increase in rates of habitat loss requires an understanding of how biodiversity is distributed. Campo rupestre is an old, climatically buffered, and infertile landscape located in Brazil. Considered a biodiversity hotspot, the campo rupestre is mainly threatened by mining activity that requires a large operating area. Campo rupestre is known for its restricted distribution area and high abiotic heterogeneity, which modulates species coexistence and richness. To recognise the association between habitat type and plant communities, we propose to describe the floristic composition of herbaceous and shrub components in four habitats of the campo rupestre comprising quartzite and ferruginous substrate. We classified habitat types by the main surface soil features. In each habitat, we sampled ten 100-m2 plots to access information on the shrub and ten 1-m2 plots for the herbaceous component. Altogether we sampled 153 species, belonging to 38 families. The cluster analysis ordered by Sorensen metric indicates a clear distinction of species composition in the shrub component in the four habitats. However, the floristic composition of the herbaceous component was similar between the four habitats but showed a distinction when contrasting with the substrate type. Our results highlight the local taxonomic distinction between habitat types and substrates, indicating that the ecological distinction among substrate types of the campo rupestre cannot be overlooked in conservation and restoration actions.